Increasing block tariff electricity pricing and the propensity to purchase dirty fuels: Empirical evidence from a natural experiment - Salim Turdaliev; Karel Janda (Charles University in Prague, Institute of Economic Studies (IES), 2022)
This paper investigates the relationship between the increasing-block-tariffs (IBT) for electricity, and the propensity of households to purchase dirty fuels. We combine RLMS-HSE, a panel household data, with the introduction of the IBT schemes for residential electricity in three experimental regions of Russia to analyze this relationship. Using differences-in-differences empirical specifications we find that the propensity to purchase dirty fuels has increased in the regions where the IBT schemes were introduced. Depending on the specification, and the type of household we find that the size of the increase varies from more than 3-percentage points to about 15-percentage points. This accounts for a roughly 70% increase, and a 90% increase respectively compared to the similar households in the regions that did not implement IBT pricing schemes for residential electricity. The empirical evidence from this paper suggests that the environmental benefits that result from the implementation of the IBT pricing schemes may be overstated if the possible negative environmental impacts of switching to more affordable, but hazardous energy sources by the population as a response to the tariff-shifts are not taken into account by the policymakers.
Keywords: Q41; Q48; L98; L94; 330; residential electricity pricing; increasing-block-tariffs; CO2 emissions; dirty fuels; transition economy; natural experiment